«Não somos nenhum protetorado italiano»: il dibattito sull’organizzazione sindacale nell’Estado Novo di Getúlio Vargas - Leo Pavesi (Laboratoire Italien)
Brazilian historians have long taken a mainly comparative approach to whether the corporatist and social legislation of the Era Vargas (1930-1945) represented an original effort or a mere ‘copy’ of the fascist model. Adopting a transnational perspective, the article not only traces the concrete process of transfer through which fascist corporatist ideas circulated among the Brazilian political elites, but it also explores the different receptions of the Italian trade union model during the early years of the Estado Novo. The debate on the enquadramento sindical saw the authoritarian thinker Oliveira Vianna, the Ministério do Trabalho and the paulista industrialists defending different and clashing solutions that shared, however, the proclaimed will of crafting a corporatist union system that should be faithful not to the fascist model, but to the socioeconomic reality of the country. ‘We are not an Italian protectorate […] we are not Libya or Abyssinia’, Oliveira Vianna wrote in 1940. Therefore, the article aims to highlight the many Brazilian receptions of the fascist corporatist model: a model, which criticised for its totalitarian and statist tendencies, was selectively adapted to the Brazilian context and often interacted with other corporatist options, such as social Catholicism.